New data on abundance of lemon shark Negaprion brevirostris (Poey, 1868) at Lama Bay, Rocas Atoll, Brazil (Ocean and Coastal Research, 2024)
The abundance and movement patterns of lemon sharks (Negaprion brevirostris) at Lama Bay, BiologicalReserve Rocas Atoll, were reassessed by visual census. We considered tides and daylight periods to plan ourobservations during two expeditions in 2015. Using daily visual counts, the mean abundance of individuals was29 in austral summer (maximum 35) and 31 in winter (maximum 41). The results indicated that the local lemonshark population might have recovered after 18 years of a substantial drop in mean abundance. In addition,the movement pattern of the species corroborated previous studies related to their fidelity to the birthplace.These results justify the need of continuous monitoring of lemon sharks over the course of time at Rocas Atollusing non-lethal and non-invasive techniques.